Blue Liquid Lasers from Solution of CdZnS/ZnS Ternary Alloy Quantum Dots with Quasi‐Continuous Pumping. (18th September 2014) - Wang, Yue; Leck, Kheng Swee; Ta, Van Duong; Chen, Rui; Nalla, Venkatram; Gao, Yuan; He, Tingchao; Demir, Hilmi Volkan; Sun, Handong
<x xml:space="preserve">Abstract</x> A blue (ca. 440 nm) liquid laser with an ultra‐low threshold through which quasi‐continuous wave pumping is accessible is achieved by engineering unconventional ternary CdZnS/ZnS alloyed‐core/shell QDs. Such an achievement is enabled by exploiting the novel gain media with minimal defects, suppressed Auger recombination, and large gain cross‐section in combination with high‐quality‐factor whispering gallery mode resonators. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>